Retirement pathways and pensions inequality in China: A grounded theory study - Timonen, Virpi (My University, 2021)
Purpose: Existing research focuses on the pension systems and reforms in China from a macro-level and financial perspective. The expectations of mid-life Chinese people regarding their retirement and pensions have been ignored to date, and our research set out to address this lacuna. Methodology: The application of qualitative research methods is relatively novel in Chinese social science. As a Grounded Theory (GT) study, the research reported here deployed semi-structured interviews to investigate middle-aged Chinese women’s and men’s perceptions of their pensions and retirement. Thirty-six interviews were conducted, following the constructivist GT method.Findings: The data point to disparities between the choices and perceptions of individuals on the one hand and the official assumptions underlying the current pension regime on the other hand. Research participants had varying interpretations of the inequality in retirement incomes in China, the main division being between enterprise workers and public sector employees. Originality: Although there are in principle rigidly fixed retirement ages for menand women in contemporary China, the phenomena of early retirement and working post-retirement are increasing. There are trade-offs between work/retirement and familyneeds which influence the choices of middle-aged citizens. Retirement pathways are increasingly individualised, reflecting broader patterns of individualisation and inequality in China.
Keywords: Ageing; China; Pensions; Retirement; Grounded theory; Ageing; Inclusive Society